On the functionalization of benzo[e][2,1]thiazine - Popov, Kirill; Volovnenko, Tatyana; Volovenko, Julian (Beilstein Journal of Organic Chemistry, 2009)
The reactions of benzo[e][2,1]thiazine-4-chloro-3-carbaldehydes 1 and benzo[e][2,1]thiazine-4-chloro-3-carbonitriles 2 with a number of oxidizing and reducing agents are reported. A number of new, highly functionalized benzo[e][2,1]thiazine derivatives having potential biological activity were synthesized and described.
Keywords: heterocycles; nucleophilic aromatic substitutions; oxidation; reduction; regioselectivity